Faktor-Faktor yang mempengaruhi laba perusahaan asuransi yang terdaftar di Bursa Efek Indonesia Periode 2013-2016 - Lia Diyuni; Ardi Paminto; Isna Yuningsih (Fakultas Ekonomi Dan Bisnis Universitas Mulawarman, 2018)
The purpose of this research is to understand whether RBC, Underwritting’s result, investment benefit, premium accumulation and the customer’s claim have significant influence to the Insurance Company’s profit which is registered in stock exchange Indonesia. There are several samples which are used in 10 registered Insurance Company with standar qualification. The analytical data is used using Uji Asumsi Klasik (Uji Normalitas and Uji Multikolinieritas), Analysis Regresi Linier Berganda, Uji autokorelasi and Uji Koefisien Determinasi. Uji F and Uji T are used for the result of hypothetical test. This research is known as the quantitative research where the data which is used is the secondary data in the form of finance’s report perion 2013-2016 which is retrieved from the official website from each 10 Insurance Company as the object in this research. And based on result of Uji T show that RBC, Investment Result and Acceptance of Premium partially or respectively have positive and significant effect to Profit. For Underwriting Results has a positive but no significant impact on earnings, while Claim Expense partially has no significant effect on the profit of insurance companies